Adhesion of Plasmodium falciparum infected erythrocytes in ex vivo perfused placental tissue: a novel model of placental malaria. (December 2016) - Pehrson, Caroline; Mathiesen, Line; Heno, Kristine; Salanti, Ali; Resende, Mafalda; Dzikowski, Ron; Damm, Peter; Hansson, Stefan; King, Christopher; Schneider, Henning; Wang, Christian; Lavstsen, Thomas; et al.
Abstract Background Placental malaria occurs whenPlasmodium falciparum infected erythrocytes sequester in the placenta. Placental parasite isolates bind to chondroitin sulphate A (CSA) by expression of VAR2CSA on the surface of infected erythrocytes, but may sequester by other VAR2CSA mediated mechanisms, such as binding to immunoglobulins. Furthermore, other parasite antigens have been associated with placental malaria. These findings have important implications for placental malaria vaccine design. The objective of this study was to adapt and describe a biologically relevant model of parasite adhesion in intact placental tissue. Results The ex vivo placental perfusion model was modified to study adhesion of infected erythrocytes binding to CSA, endothelial protein C receptor (EPCR) or a transgenic parasite whereP. falciparum erythrocyte membrane protein 1 expression had been shut down. Infected erythrocytes expressing VAR2CSA accumulated in perfused placental tissue whereas the EPCR binding and the transgenic parasite did not. Soluble CSA and antibodies specific against VAR2CSA inhibited binding of infected erythrocytes. Conclusion The ex vivo model provides a novel way of studying receptor-ligand interactions and antibody mediated inhibition of binding in placental malaria.